Innovation in Waste Management Methods for Sustainable Tourism (A Case Study at Pullman Hotel Lombok) - Veronica, Veronica; Tirtadidjaja, Andari; Michaela, Janice Aveline (Riwayat: Educational Journal of History and Humanities, 2025)
Sustainable tourism has become a key focus in the development of the global tourism industry, with Lombok as a major destination facing challenges in waste management. Ineffective waste management threatens environmental sustainability, the quality of tourist destinations, and has negative impacts on the surrounding communities. Therefore, innovation in waste management within the hospitality sector is crucial to support the principles of sustainable tourism. Pullman Hotel Lombok has adopted the Green Hotel initiative to minimize environmental impacts through eco-friendly waste management. This research aims to explore waste management innovations at this hotel, focusing on waste segregation, the processing of food waste into organic liquid fertilizer, and their impact on environmental sustainability and hotel operations. The research methodology includes in-depth interviews with management and relevant staff to identify the waste management practices implemented. The findings reveal that waste management innovations at Pullman Hotel Lombok successfully reduce waste volume, improve soil quality, and decrease greenhouse gas emissions, supporting the achievement of Sustainable Development Goals (SDGs). This study recommends developing more efficient waste management technologies and enhancing local community awareness through continuous training programs to promote sustainable practices in the hospitality and tourism sectors.